Analisa Produktivitas Tenaga Kerja Pada Proyek Pembangunan Gedung Bertingkat Dengan Menggunakan Metode Time Study (Studi Kasus: Proyek Pembangunan Gedung Kejaksaan Tinggi Kalimantan Tengah): Analysis Of Labor Productivity In Multi-Story Building Construction Projects Using Time Study Method (Case Study: Construction Project Of The High Prosecutor’s Office In Central Kalimantan) - Crish, Crish; Respati, Rida; Saputra, Norseta Ajie (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The productivity of workers determines the success of the implementation of the construction project schedule, because it has an impact on the compatibility between the planning of the construction schedule and the progress of work in the field. The worker productivity that will be calculated is the work of reinforcing beams in the Central Kalimantan High Prosecutor's Office building construction project. The calculation of worker productivity will be carried out using the time study method.This study aims to determine the extent of worker productivity during working hours in the morning and evening. The method used in this research is the time study method, which is the measurement of labor productivity in the field by determining the standard time of a job. From this method can be seen the comparison of worker productivity from the results of a job. In this case study, the factors that affect worker productivity will be identified. The data collection technique in this study used a questionnaire by giving written questions to respondents that were relevant to the research objectives. Based on the results of the analysis, it is known that the productivity of workers in the morning higher with an average weight of 41,825 kg/hour than in the afternoon of 40,433 kg/hour. Where on the first day the productivity of morning workers is 12,56% and in the afternoon it is 11,97%. On the second day the productivity of morning workers is 12,81% and in the afternoon it is 12,18%. On the third day the productivity of morning workers is 12,68% and in the afternoon 12,43%. On the fourth day the productivity of morning workers is 12,85% and in the afternoon 12,52%. In general, it can be seen that the productivity of workers in the morning is higher than that of workers in the afternoon. There are 3 categories of factors that influence worker productivity: not influential (TB) are wind gusts; influential (B) are weather factors; number of workers, age, wages; managerial factors; effectiveness of working hours; and very influential are skill factors